Analysis of technological, organizational, environmental, and digital adoption factors on the net benefit of the mses sector in east java-indonesia - Aris Kusumawati; Ully Asfari; Aisyah Putri Amni Ramadhanti; Ekky Dea Audry Jaya; Farid Duta Hadyanto (Institute of Computer Science (IOCS), 2023)
Digital transformation is a necessity for organizations in the current new normal era. Most organizations have successfully adapted and continued to carry out business activities during the crisis due to the Covid-19 pandemic by carrying out digital transformation. Digital transformation is challenging to implement in small-scale organizations, especially the MSME sector, which has many limitations. So, the success of digital transformation in the MSME sector is still in doubt. To examine this phenomenon, this research proposed a conceptual model developed based on TOE and D&M (DeLone and McLean). Using quantitative methods in the new normal era, the proposed conceptual model aims to determine how technological, organizational, environmental, and digital adoption influences net benefits in the MSME sector. The survey has been distributed online to the MSME sector in East Java. It obtained 400 respondent data based on a random sampling technique and analyzed using PLS-SEM. Based on the conceptual model, the researcher has proposed four hypotheses that have been tested using PLS. The results of this research found that technological, organizational, environmental, and digital adoption positively affected net benefits in the MSME sector. The four proposed hypotheses are proven.